The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/foods11071049
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Whey Protein—Citrate Mung Bean Starch—Capsaicin Microcapsules by Spray Drying with Improved Stability and Solubility

Abstract: Capsaicin was microencapsulated in six different wall systems by spray drying whey protein and citrate mung bean starch at various ratios (10:0, 9:1, 7:3, 5:5, 3:7, 1:9, 0:10) to improve its stability and water solubility and reduce its pungency. The morphological, rheological, storage stability, and physicochemical properties of capsaicin emulsion and capsaicin microcapsules were characterized. As a result, the yield of six capsaicin microcapsules was 19.63–74.99%, the encapsulation efficiency was 26.59–94.18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
(52 reference statements)
1
3
0
1
Order By: Relevance
“…This was consistent with the research of Zhang et al [26]. Additionally, when comparing the results with Zhang et al [27], it was found that the experimental results were consistent in terms of an encapsulation layer that formed around the core material, resulting in a higher encapsulation efficiency with an increasing concentration of GA in the coating material. The encapsulation efficiency of capsaicin microcapsules from capsicum using WPI Figure 6.…”
Section: ) Chemical Performance Test In Encapsulation Of the Microcap...supporting
confidence: 91%
“…This was consistent with the research of Zhang et al [26]. Additionally, when comparing the results with Zhang et al [27], it was found that the experimental results were consistent in terms of an encapsulation layer that formed around the core material, resulting in a higher encapsulation efficiency with an increasing concentration of GA in the coating material. The encapsulation efficiency of capsaicin microcapsules from capsicum using WPI Figure 6.…”
Section: ) Chemical Performance Test In Encapsulation Of the Microcap...supporting
confidence: 91%
“…Zhang et al . (2022a, 2022b) reported that the EE of capsaicin microcapsules ranged from 26.59% to 94.18%. In this study, the EE of the capsaicin microcapsule system was in the range of 73.20% to 84.05% (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…While the L* was the lowest value of 83.55 when the ratio of sodium caseinate to acetylated wheat starch was 1:9, and the colour was darker than that of the other samples. Samples with higher whiteness indicate that capsaicin was less exposed on the surface of microcapsules, with a better embedding effect and higher EE (Zhang et al ., 2022a, 2022b). The lightness was higher (91.64), and the loading rate was also higher (83.31%) when the ratio of sodium caseinate to acetylated wheat starch was 5:5 compared to the other microcapsule samples (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…El uso de la harina de frijol se ha planteado en otras investigaciones para la diversificación de productos funcionales mostrando resultados positivos de aceptación (Sánchez-Toledano et al, 2021). A su vez, la microencapsulación con partes del frijol ha evidenciado estabilidad y solubilidad, por lo que se sugiere que tiene aplicaciones potenciales en la industria alimentaria (Zhang et al, 2022).…”
Section: Introducciónunclassified